3-[1-(4-Bromophenyl)ethoxy]-2,2,5-trimethyl-4-phenyl-3-azahexane - Anne M. Hudrlik (Acta Crystallographica Section E, 2013)
The title compound, C22H30BrNO, is an alkoxyamine compound, an effective initiator in nitroxide-mediated free radical polymerization. It was prepared as a mixture of two diasteromers; the crystal for the X-ray analysis showed one of these as a pair of R,S and S,R enantiomers. The tert-butyl and isopropyl groups are in an almost anti conformation in the crystal [C—N—C—C torsion angle = −168.8 (1)°], and the methyl group of the ethoxy group is in an approximate anti relationship to the tert-butyl group. The dihedral angle between the phenyl and benzene rings is 33.12 (7)°. The Br atom is disordered over two positions, with occupancies of 0.9139 (16) and 0.0861 (16). In the crystal, weak C—H...Br contacts link the molecules into chains along [-110].